PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP KUALITAS SUMBER DAYA MANUSIA - Imawi, Amylia Yulytianing; Prasetiya, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Humans are the foundation of the development process, so improving the quality of human resources for the better will have a good impact on development. This study aims to examine the effect of regional original income, balancing funds, and excess budget financing on the quality of human resources. This type of research is a quantitative research using secondary data on regional government financial reports obtained from DJPK and statistical data from BPS. The object of this research covers all 38 regencies/cities in East Java in 2015-2021 using Path analysis using Stata17. The results of the study show that regional original income and SILPA have an influence on the quality of human resources. SILPA have an effect on the quality of human resources through capital expenditure. The implication of the results of this test is that local governments must increase local revenue and reduce balance funds, as well as allocate excess budget financing so that it has an impact on improving the quality of human resources through planned policies.